A Novel Nonsense Mutation of ABCA8 in a Han-Chinese Family With ASCVD Leads to the Reduction of HDL-c Levels - Wang, Chen-Yu; Chen, Ya-Qin; Jin, Jie-Yuan; Du, Ran; Fan, Liang-Liang; Xiang, Rong (Frontiers in Genetics, 2020)
Arteriosclerotic cardiovascular disease (ASCVD) is one of the major causes of death worldwide and most commonly develops as a result of atherosclerosis (AS). As we all know, dyslipidemia is a leading pathogenic risk factor for ASCVD, which leads to cardiac ischemic injury and myocardial infarction. Dyslipidemias include hypercholesterolemia, hypertriglyceridemia, increased low-density lipoprotein cholesterol (LDL-c) and decreased high density lipoproteins cholesterol (HDL-c). Mutations of dyslipidemia related genes have been proved to be the crucial contributor to the development of AS and ASCVD. In this study, a Han-Chinese family with ASCVD was enrolled and the lipid testing discovered an obvious reduced levels of HDL-c in the affected members. We then performed whole exome sequencing to detect the candidate genes of the family. After data filtering, a novel heterozygous nonsense mutation (NM_007168: c.3460C>T; p.R1154X) of ABCA8 was detected and validated to be co-separated in the family members by Sanger sequencing. Previous studies have proved that deleterious heterozygous ABCA8 variants may disrupt cholesterol efflux and reduce HDL-c levels in humans and mice. This study may be the second report related to ABCA8 mutations in patients with reduced levels of HDL-c. Our study not only contributed to the genetic counseling and prenatal genetic diagnosis of patients with ASCVD caused by reduced HDL-c levels, but also provided a new sight among ABCA8, cholesterol efflux and HDL-c levels.